2002
DOI: 10.1128/iai.70.10.5363-5369.2002
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses to Novel Pneumococcal Proteins Pneumolysin, PspA, PsaA, and CbpA in Adenoidal B Cells from Children

Abstract: Studies of mice suggest that pneumococcal proteins, including PspA, pneumolysin, PsaA, and CbpA, are promising vaccine candidates. To determine whether these proteins are good mucosal immunogens in humans, adenoidal lymphocytes from 20 children who had adenoidectomies were isolated and tested by ELISpot for antigen-specific antibody-secreting cells (ASCs). Cells were also cultured for 7 days in the presence of a concentrated culture supernatant (CCS) from a type 14 strain of pneumococcus which contained secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 51 publications
3
47
0
Order By: Relevance
“…Since IgGproducing plasma cells are scarce in salivary glands, and it has been shown that that immunocytes, especially IgG-secreting cells, are present in significant numbers in surface secretion on adenoids) [35,36], this may represent an additional source of immunoglobulin in local mucosal secretions including saliva. We have previously reported that adenoids commonly contain significant numbers of antibody-secreting cells to the pneumococcal protein antigens studied here [28]. Another possibility is that contact between the sponge swab and the oral mucosa increased passive transudation from serum to a variable extent, thus explaining the unexpectedly high concentrations of IgG to some antigens in some individuals' saliva.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Since IgGproducing plasma cells are scarce in salivary glands, and it has been shown that that immunocytes, especially IgG-secreting cells, are present in significant numbers in surface secretion on adenoids) [35,36], this may represent an additional source of immunoglobulin in local mucosal secretions including saliva. We have previously reported that adenoids commonly contain significant numbers of antibody-secreting cells to the pneumococcal protein antigens studied here [28]. Another possibility is that contact between the sponge swab and the oral mucosa increased passive transudation from serum to a variable extent, thus explaining the unexpectedly high concentrations of IgG to some antigens in some individuals' saliva.…”
Section: Discussionmentioning
confidence: 94%
“…We have previously shown that antibody-secreting cells to pneumococcal protein antigens are present among adenoidal mononuclear cells (MNC) isolated from children undergoing adenoidectomy, suggesting that these pneumococcal proteins prime specific B cells for production of specific IgA, IgG and IgM antibodies in these children [28]. Here we report antibody responses to pneumococcal protein antigens in serum, saliva and adenoidal MNC after in vitro antigen stimulation in relation to carriage status in children.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…To our knowledge, the present study provides the first confirmation that B cell memory is never established against linear epitopes of VP2 and adds further credence to the concept that long-lived plasma cells and memory B cells are 2 separate forms of independently controlled immunological memory [20,21]. A recent report of the enumeration, in the adenoids of children, of IgG memory B cells against 4 pneumococcal antigens has also shown a broad antigen-specific response, which suggests that certain antigens are more likely than others to elicit the establishment of B cell memory [22]. It is also likely that the B19-specific B cell ELISpot assay could find application in the confirmation of past infection with B19.…”
Section: Discussionmentioning
confidence: 99%